2022
DOI: 10.3390/d14040262
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcodes for Accurate Identification of Selected Medicinal Plants (Caryophyllales): Toward Barcoding Flowering Plants of the United Arab Emirates

Abstract: The need for herbal medicinal plants is steadily increasing. Hence, the accurate identification of plant material has become vital for safe usage, avoiding adulteration, and medicinal plant trading. DNA barcoding has shown to be a valuable molecular identification tool for medicinal plants, ensuring the safety and efficacy of plant materials of therapeutic significance. Using morphological characters in genera with closely related species, species delimitation is often difficult. Here, we evaluated the capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Recent investigations indicated that the plant-based antioxidants have been known to shield humans from a few prolonged ailments, for example, aggravation, immune system sicknesses, malignancy, and tumor arrangement by preventive the production of free radicals [ 12 ]. The research on plants has been increasing worldwide, and scientific data collected so far reflects the use of medicinal plants in many traditional systems [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations indicated that the plant-based antioxidants have been known to shield humans from a few prolonged ailments, for example, aggravation, immune system sicknesses, malignancy, and tumor arrangement by preventive the production of free radicals [ 12 ]. The research on plants has been increasing worldwide, and scientific data collected so far reflects the use of medicinal plants in many traditional systems [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have estimated the amplicon universality and the success rate of amplification of various chloroplast–plastid (<90%) and nuclear genes (80%) in the rare taxa, Eryngium . Previous reports showed a low amplification rate of 60% in matK for species discrimination in other medicinal plants [ 12 ]. Molecular phylogeny analyzes the genetic heredity based on the DNA sequences to understand the evolutionary interrelationship, deriving the genetic diversity among the species.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characterization using random DNA markers showed a compressive genetic variability among the genotypes. However, DNA barcoding is an advanced tool to investigate variations at the most conserved region to specify accurate species delimitation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional combinations of markers, including rbcL + trnH-psbA, trnH-psbA + ITS2, and matK + trnH-psbA, have also been assessed for their efficiency in discrimination and universality of species identification (Kress et al, 2005;Kress and Erickson, 2007;Li et al, 2012;Tripathi et al, 2013;Mishra et al, 2015;Mahima et al, 2020). Evaluation of the reports related to multiple loci DNA in plant identification revealed that, the combined loci of ITS2 and trnH-psbA were found to be the best two-marker combination for the identification of plants and even herbal samples (Zuo et al, 2011;Vassou et al, 2015;Jamdade et al, 2022). By employing the combined barcode loci a deep phylogenetic tree can be established, which could be applied in the identification of species and also discrimination of closely related species.…”
Section: Multiple-locus Dna Barcode Markersmentioning
confidence: 99%